2016
DOI: 10.1007/s00253-016-7454-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extracellular pH on growth, viability, cell size, acidification activity, and intracellular pH of Lactococcus lactis in batch fermentations

Abstract: In this study, we investigated the influence of three extracellular pH (pHex) values (i.e., 5.5, 6.5, and 7.5) on the growth, viability, cell size, acidification activity in milk, and intracellular pH (pHi) of Lactococcus lactis subsp. lactis DGCC1212 during pH-controlled batch fermentations. A universal parameter (e.g., linked to pHi) for the description or prediction of viability, specific acidification activity, or growth behavior at a given pHex was not identified. We found viability as determined by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…In their study, Hansen et al . () correlated low Lc. lactis acidification activities with decreasing cell sizes observed upon entry into stationary phase during fermentations carried out at pH 6·5 and 7·5, but not at pH 5·5.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In their study, Hansen et al . () correlated low Lc. lactis acidification activities with decreasing cell sizes observed upon entry into stationary phase during fermentations carried out at pH 6·5 and 7·5, but not at pH 5·5.…”
Section: Discussionmentioning
confidence: 78%
“…lactis concentrates produced during batch fermentation (Hansen et al . ). Highest acidification activities were achieved at low pH (pH 5·5) and the negative effect of increasing harvest times during stationary phase was only seen at high pH (pH 6·5 and 7·5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Langheinrich and Nienow (1999) reported pH gradients of 0.8 units due to alkali addition in an 8 m 3 reactor for mammalian cell cultures. The extracellular pH affects the intracellular pH of lactic acid bacteria (Cachon, Antérieux, & Diviès, 1998;Hansen et al, 2016) and by this the enzymatic activity. Aghababaie et al (2015) reported that the growth of S. thermophilus was reduced by 20% when cultivated 0.3 pH units away from the optimal pH conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Aghababaie et al (2015) reported that the growth of S. thermophilus was reduced by 20% when cultivated 0.3 pH units away from the optimal pH conditions. In the immediate vicinity of the inlet for base addition, the cells are exposed to unfavorable pH values that might lead to viability loss (Hansen et al, 2016). Cortés et al (2016) and Amanullah et al (2001) showed in two-compartment scale-down studies of E. coli and B. subtilis, in which they mimicked oscillating pH conditions up to a delta pH of 0.9, that growth was not statistically significantly affected.…”
Section: Discussionmentioning
confidence: 99%